Comparison of Wealth Management Models Used in India - Arora, Palka (2006)
The last few years have seen a boom in financial markets in the developing world. After the opening up of the Indian economy in 1991, it has seen a stupendous inflow of outside money in the financial markets. Last few years have changed the investment picture of India completely. It is one of the most preferred investment destinations. Be it real estate or mutual funds or private equity, foreign hedge funds, institutional investors and private equity companies have made India a hot investment market. As a result the Indian investor's pockets are quite full and they are themselves worried about managing their own capital, not only because of the increase in their wealth but also due to coming of confusing and complicated investment products. Wealth management industry is very new to this country, it has mainly been brought in by the foreign banks. With time, many small players are also growing in this market and trying to compete with the major market share holders. Wealth management may be defined as the coordination of a client's investment, tax and estate plans into a comprehensive plan to achieve their personal goals. There are so many professional portfolio managers who coordinate their customer's investments in such a way that they achieve their client's personal goals. There is always an argument going on between the active portfolio managers and the passive portfolio managers. Wealth management is a complete study in itself. The basic steps involved include analyzing the needs of the customers, cater and provide for the future goals and objectives of the customer, product selection and asset allocation based on the goals to be achieved and available wealth for investment. This research will study three wealth management models used by Citibank, HSBC and HDFC Banks in India and try to make a comparative analysis between them. This report also develops a new model based on the models studied encompassing their good points and proves that the practical models used in the market today are based on the literature theories.